+0  
 
0
727
1
avatar

-17 -     = -6

 18.08.2015

Beste Antwort 

 #1
avatar+13573 
+5

Hallo anonymous!

 

- 17 -    = - 6                   Die fehlende Zahl sei x .

 

- 17 - x = - 6                   [ * (- 1)  beide Seiten

17 + x = 6                      [ - 17      beide Seiten

x = 6 - 17                       [ 6 - 17 = - (17 - 6) 

x = - 11

 

- 17 - (- 11) = - 6

 

:- )

 18.08.2015
 #1
avatar+13573 
+5
Beste Antwort

Hallo anonymous!

 

- 17 -    = - 6                   Die fehlende Zahl sei x .

 

- 17 - x = - 6                   [ * (- 1)  beide Seiten

17 + x = 6                      [ - 17      beide Seiten

x = 6 - 17                       [ 6 - 17 = - (17 - 6) 

x = - 11

 

- 17 - (- 11) = - 6

 

:- )

asinus 18.08.2015

14 Benutzer online

avatar
avatar